[Prolonged pain in neonates: retrospective analysis] - Lilla, M.; Stadelman-Diaw, C.; Ramelet, Anne-Sylvie (2013)
INTRODUCTION: Infants hospitalised in neonatology are inevitably exposed to pain repeatedly. Premature infants are particularly vulnerable, because they are hypersensitive to pain and demonstrate diminished behavioural responses to pain. They are therefore at risk of developing short and long-term complications if pain remains untreated. CONTEXT: Compared to acute pain, there is limited evidence in the literature on prolonged pain in infants. However, the prevalence is reported between 20 and 40 %. OBJECTIVE: This single case study aimed to identify the bio-contextual characteristics of neonates who experienced prolonged pain. METHODS: This study was carried out in the neonatal unit of a tertiary referral centre in Western Switzerland. A retrospective data analysis of seven infants' profile, who experienced prolonged pain, was performed using five different data sources. RESULTS: The mean gestational age of the seven infants was 32weeks. The main diagnosis included prematurity and respiratory distress syndrome. The total observations (N=55) showed that the participants had in average 21.8 (SD 6.9) painful procedures that were estimated to be of moderate to severe intensity each day. Out of the 164 recorded pain scores (2.9 pain assessment/day/infant), 14.6 % confirmed acute pain. Out of those experiencing acute pain, analgesia was given in 16.6 % of them and 79.1 % received no analgesia. CONCLUSION: This study highlighted the difficulty in managing pain in neonates who are exposed to numerous painful procedures. Pain in this population remains underevaluated and as a result undertreated. Results of this study showed that nursing documentation related to pain assessment is not systematic. Regular assessment and documentation of acute and prolonged pain are recommended. This could be achieved with clear guidelines on the Assessment Intervention Reassessment (AIR) cycle with validated measures adapted to neonates. The adequacy of pain assessment is a pre-requisite for appropriate pain relief in neonates.